The Pullout Performance of Pedicle Screws - Demir, Teyfik; Basgül, Cemile (SpringerBriefs in Computational Mechanics,, 2015)
This brief book systematically discusses all subjects that affect the pullout strength of pedicle screws. These screws are used in spinal surgeries to stabilize the spine. The holding strength of the pedicle screw is vital since loosening of the pedicle screws can cause revision surgeries. Once the pedicle screw is pulled out, it is harder to obtain same stabilization for the fused vertebrae. The book reviews the effect of screw designs, application techniques, cement augmentation, coating of the screw and test conditions on the pullout strength. The studies with finite element analysis were also included.